THE RELATIONSHIP BETWEEN ADOLESCENTS' KNOWLEDGE LEVELS OF SEXUAL DEVELOPMENT AND ANTICIPATION OF THE RISK OF SEXUAL HARASSMENT - Fadliyah, Lailatul; Puspitaningtyas, Danty Indra; Sulpat, Emuliana; Mardhika, Amellia; Sarofah, Eka; Ma'rifah, Umi; Nur Rochmayanti, Shinta (Journal of Vocational Nursing, 2024)
Introduction: Adolescence is a transition period from childhood to adulthood that includes changes both biologically, intellectually, psychosocially, and economically. In this period, individuals have reached sexual and physical maturity. Negative behavior carried out by adolescents is risky behavior in having sexual intercourse. The purpose of this study was to determine the relationship between the level of adolescent knowledge about the development of sexuality (physical changes) and anticipation of the risk of sexual harassment. Methods: This research is an analytical research with a cross-sectional design. Population in this study were 92 junior high school students in grades 7 and 8 in Kediri Regency. Sampling technique used was Purposive sampling, with a sample size of 80 students. The data collection technique used a questionnaire. The analysis test used was the Chi-Square Test. Results: Results of the study found that 47 respondents had low knowledge levels (58.75%), and 46 respondents had poor anticipation of sexual harassment (78.0%). Bivariate analysis with Chi-Square obtained p value = 0.000 (significance t < 0.05). Conclusions: There is a relationship between the level of adolescent knowledge about sexual development (physical changes) and anticipation of the risk of sexual harassment.